1992
DOI: 10.1210/jcem.75.3.1517377
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone-binding proteins of human serum: developmental patterns in normal man.

Abstract: The binding of GH by a low affinity binding protein (LA-BP) was measured from birth into adulthood and compared with binding of a high affinity binding protein (HA-BP) in human serum. Pooled serum samples for each year of age from birth to 16.5 yr were formed from 2500 separate samples and assayed for both binding proteins using a Sephadex chromatographic method. Individual samples in this age range and those from adults were assayed in a similar manner. Binding of [125I]GH was minimal by both binding proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Our findings in healthy children are in accordance with most previous reports in which it has been suggested that the childhood‐related increase in GHBP occurs primarily in prepuberty (Silbergeld et al ., 1989; Massa et al ., 1992a; Merimee et al ., 1992; Martha et al ., 1993). In contrast, Carlsson and coworkers have reported a significant increase in GHBP serum levels in puberty in their study of 733 healthy children (Carlsson et al ., 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings in healthy children are in accordance with most previous reports in which it has been suggested that the childhood‐related increase in GHBP occurs primarily in prepuberty (Silbergeld et al ., 1989; Massa et al ., 1992a; Merimee et al ., 1992; Martha et al ., 1993). In contrast, Carlsson and coworkers have reported a significant increase in GHBP serum levels in puberty in their study of 733 healthy children (Carlsson et al ., 1994).…”
Section: Discussionmentioning
confidence: 99%
“…In newborns GHBP levels are very low until to 2-6 months of life, followed by a more steep increase up till age 2 years and a more gradual increase throughout childhood with maximum levels attained in early adulthood [73,[133][134][135]. Different and in part opposing correlations are described between GHBP and various measures of growth in children.…”
Section: Age and Timementioning
confidence: 97%